Nermin Yildirim’s Sakli Bahçeler Haritasi (The Hidden Gardens Map) in the Context of Multiple Personality Disorder - Nazlı Memiş Baytimur (Humanities)
Novels, which take shape in imaginary worlds, are closely connected to life and reality. Psychiatric disorders also belong to life and reality and are part of the content of literary works. Authors sometimes make use of mental disorders to tell a story or to give depth to fiction. Such disorders, which started to be seen in Turkish literature in the novels of the Tanzimat period, play particularly dramatic roles in texts produced after the 1960–1970s. Psychological disorders include dissociative disorders, one type of which is multiple personality disorder. The person experiencing this type of dissociation develops two or more independent personality systems in response to feelings of anxiety. One of the most important works of recent Turkish literature, Nermin Yıldırım’s Saklı Bahçeler Haritası (The Hidden Gardens Map), first published in 2013, is a novel in which multiple personality disorder plays a significant role. This study attempts to determine how the defining criteria and symptoms of multiple personality disorder are exhibited in the aforementioned novel and how its effects and related issues are conveyed to the reader.